Https://botryosphaeriales.org/, an online platform for up-to-date classification and account of taxa of Botryosphaeriales. (15th October 2021) - Wu, N a; Dissanayake, Asha J; Manawasinghe, Ishara S; Rathnayaka, Achala R; Liu, Jian-Kui; Phillips, Alan j.l; Promputtha, Itthayakorn; Hyde, Kevin D
Abstract: Fungi are eukaryotes that inhabit various ecosystems worldwide and have a decomposing effect that other organisms cannot replace. Fungi are divided into two main groups depending on how their sexual spores are formed, viz. Ascomycota and Basidiomycota. The members of Botryosphaeriales (Dothideomycetes, Ascomycota) are ubiquitous. They are pathogenic on a wide range of hosts, causing diverse diseases including dieback, canker, leaf spots and root rots and are also reported as saprobes and endophytes worldwide. As an important fungal group, of which most are plant pathogens, it is necessary to organize data and information on Botryosphaeriales so that scientific literature can be used effectively. For this purpose, a new website, https://botryosphaeriales.org is established to gather all published data together with updates on the present taxonomy of Botryosphaeriales. The website consists of an easy-to-operate searching system and provides an up-to-date classification together with accounts of Botryosphaeriales taxa, including colour illustrations, descriptions, notes and numbers of species in each genus, as well as their classification. Thus, readers will be able to obtain information on botryosphaerialean taxa through this platform. Database URL: https://botryosphaeriales.org/